PENGARUH KOMUNIKASI NONVERBAL DOSEN TERHADAP MINAT BELAJAR MAHASISWA - Abdul Haliq; Mardiyanah Nasta (Universitas Negeri Makassar, 2016)
Abstract: Effect of Interest Nonverbal Communication Teaching Students Learn. The aim of this research was to determine the effect of nonverbal communication lecturer to student interest in learning the Indonesian education courses. The approach in this study is a quantitative research. The research was conducted on two different courses, namely Indonesian Education Program. These courses are within the scope of the Faculty of Languages and Literature, University of Makassar. In this study, data collection was done by questionnaire and interview. The data collection was conducted to obtain data on the effect of nonverbal communication to the interest of students learning Indonesian Education Faculty of Languages and Literature, University of Makassar force in 2014. In this study, the data collected through questionnaires and interviews were subsequently analyzed by quantitative descriptive and to use the influence menanalisis SPSS program in order to determine the extent of nonverbal communication pengruh lecturer with student motivation to learn. Results of linear regression analysis to test the hypothesis indicates that the value t count> t-table (8072> 2363). From the test results concluded that there is significant influence between nonverbal communication lecturer to student interest in learning.